T2 cytokine-driven alarmin and antiviral responses in asthma: insights into immune modulation and the role of IL-4Rα targeting - Jelena Pesic; Juan José Nieto-Fontarigo; Juan José Nieto-Fontarigo; Katerina Pardali; Stephen Delaney; Henric Olsson; Lena Uller (Frontiers in Allergy)
IntroductionSevere asthma is a heterogeneous condition characterized by distinct phenotypes and endotypes based on clinical or biological characteristics. Interleukin (IL) 4 and IL-13 are central cytokines in the type 2 (T2) immune response, crucial for T2 inflammation. Biologic therapies targeting the IL-4/IL-13 pathway, such as anti-IL-4Rα monoclonal antibodies (mAbs), have shown improvements in lung function and reductions in exacerbation rates for severe asthma. However, the precise role of early innate immune responses in mediating these therapeutic benefits remains unclear. This study investigates the acute and chronic effects of T2 cytokines on healthy and asthmatic bronchial epithelial cells (BECs), addressing the mechanisms underlying IL-4Rα mAb therapy in acute T2-driven inflammatory conditions and rhinoviral infection in asthma BECs.MethodsHuman BECs from healthy and asthma donors were cultured at the air–liquid interface (ALI) and stimulated with IL-4 and IL-13, acutely or chronically, with or without IL-4Rα mAb, followed by rhinovirus (RV) infection. Cells were harvested 24 h post-infection. Expression levels of chemokines, alarmins, and antiviral mediators were quantified using RT-qPCR and multiplex ELISA.ResultsCCL26 expression increased in response to IL-4 or IL-13 in healthy and asthmatic BECs, and this effect was significantly more pronounced in asthmatic BECs. IL-4Rα mAb treatment effectively inhibited CCL26 production in BECs from asthma patients. IL-4 and RV infection induced a significant increase in thymic stromal lymphopoietin (TSLP) levels in BECs from asthma compared with healthy, which was normalized by IL-4Rα mAb. No significant effects of T2 cytokines on alarmins were observed in healthy BECs. Chronic exposure to T2 cytokines following RV infection significantly decreased TSLP and IFNλ1 but increased IFNβ, specifically in asthmatic BECs.ConclusionsOur study on T2 cytokines' effects on BECs reveals that asthma BECs have an increased inflammatory response to IL-4 and IL-13. These responses, marked by increased CCL26 and TSLP, were effectively mitigated by IL-4Rα mAb. Importantly, this treatment maintained essential antiviral defenses, such as IFNβ, even post-rhinoviral infection. Our results suggest a novel mechanism by which IL-4Rα mAb controls exacerbations and improves lung function.